Effect of Peanut Shell Torrefaction on Qualities of The Produced Bio-pellet - Santiyo Wibowo; Ningseh Lestari (Reaktor, 2018)
Peanut shells could be regarded as biomass wastes generated from agricultural products, which are abundantly available.  The current handling of those wastes is merely through direct incineration, without a proper and controlled manner. Consequently, it could arouse environmental concerns, such as air pollution and human respiratory diseases.  One alternative solution is converting those peanut shells to bio-pellet, expectedly applicable for fuels.  Relevantly, research on bio-pellet manufacture from peanut shells, previously treated with the torrefaction, was conducted. It’s aimed mainly to identify the fuel-related characteristics of bio-pellet products.  The tested bio-pellet parameters covered, moisture content, ash content, volatile matters, fixed carbon content, calorific values, and density.  The results revealed that torrefaction temperature and time at raw materials (peanut shells) could improve their qualities in regard to particular calorific value compared to those before such torrefaction; which referred to Indonesia’s Standard (SNI-8021-2014) for wood bio-pellet.  Further, torrefaction could increase bio-pellet quality which satisfied the SNI’s Standard, except for ash content.  Optimal torrefaction treatment was obtained at 300oC temperature for 60 minutes, whereby it achieved remarkable bio-pellet characteristics in terms of moisture content (3.092%), ash content (6.116%), volatile matters (38.387%), fixed carbon (55.447%), calorific value (6174 cal/g), and density (0.703 g/cm3). The torrefaction bio-pellets from peanut shells could achieve remarkable performances, with respect to fuel consumption rate (0.68 kg/hr), heating value (6174 kcal/kg), and thermal efficiency (16.67%).Keywords: biomass wastes, bio-pellet, conversion, peanut shells, torrefaction treatment